Interpretation of Irish Nationalism in The Shaughraun by Dion Boucicault , John Bull's Other Island by George Bernard Shaw, and Translations by Brian Friel - Salman Al-Sarry, Meeaad Jasim (Opción, 2019)
The study discusses interpretation of Ireland in three Irish dramas : The Shaughraun , John Bull's Other Island , and Translations. The introduction presents Ireland and the political vision which the Irish playwrights have been discussing throughout history. The Irish drama produces new and different versions of Irishness by interpreting the Irish stage. Selected scenes are taken from each play and then analyzed as far as the subject is concer- ned. Discussion and analysis start with The Shaughraun by Dion Boucicault ,then John Bull's Other Island by George Bernard Shaw , and finally Trans- lations by Brian Friel. Each play is presenting the importance of understan- ding and interpreting Ireland on stage. Such interpretation and understan- ding can be attained in showing the difficult circumstances that Ireland suffer from. Political disputes and conflicts for national identity are used by the Irish playwrights as the main themes in their drama. Finally , the study ends with the conclusion which sums up the success of the three dramas in interpreting Ireland in view of politics and nationalism as well.